Respuesta :
1. the perfect squares in this case are
a²+26a+169 = (a+13)²
a²+14a+49 = (a+7)²
2. factorising
4p²+36p+81
product = 324
sum = 36
numbers are 18 and 18
Thus , 4p²+18p+18p+81
2p(2p+9) +9p(2p+9)
thus, (2p+9p)(2p+9p)
3. Factor 81a36-64b16
this is the difference between two squares, such that;
a²-b² = (a+b)(a-b)
therefore, 81a36 -64b16 will be;
(9a18-8b8)(9a18+8b8)
4. The differences between two squares is such that;
a²-b² = (a+b)(a-b)
therefore in this case, the difference between two squares will be;
x²-169 = (a-13)(a+13), and
t²-4 = (t-4)(t+4)
a²+26a+169 = (a+13)²
a²+14a+49 = (a+7)²
2. factorising
4p²+36p+81
product = 324
sum = 36
numbers are 18 and 18
Thus , 4p²+18p+18p+81
2p(2p+9) +9p(2p+9)
thus, (2p+9p)(2p+9p)
3. Factor 81a36-64b16
this is the difference between two squares, such that;
a²-b² = (a+b)(a-b)
therefore, 81a36 -64b16 will be;
(9a18-8b8)(9a18+8b8)
4. The differences between two squares is such that;
a²-b² = (a+b)(a-b)
therefore in this case, the difference between two squares will be;
x²-169 = (a-13)(a+13), and
t²-4 = (t-4)(t+4)
Step-by-step explanation:
1. the perfect squares in this case are
a²+26a+169 = (a+13)²
a²+14a+49 = (a+7)²
First and fourth option are correct.
2. factorise 4p²+36p+81
Product = 324 and sum = 36
numbers are 18 and 18
∴ 4p²+18p+18p+81
⇒ 2p(2p+9) +9(2p+9)
⇒ (2p+9)(2p+9) ⇒ [tex](2p+9)^2[/tex]
3. Factor [tex]81a^36-64b^16[/tex]
As [tex]a^2-b^2=(a+b)(a-b)[/tex]
∴ [tex]81a^36-64b^16=(9a^18)^2-(8b^8)^2[/tex]
=[tex](9a^18-8b^8)(9a^18+8b^8)[/tex] (Option B)
4. The differences between two squares is such that;
a²-b² = (a+b)(a-b)
[tex]x^2-169=x^2-13^2=(a-13)(a+13)[/tex], and
[tex]t^2-4=t^2-2^2=(t-2)(t+2)[/tex]
First and third option correct.